Effect of Payment Gateway, Financial Literacy, Financial Inclusion On the Performance of SMEs in Mataram City - Auliana, Dhiya (Jurnal Ekonomi Kuantitatif Terapan; Vol 17 No 2 (2024): Vol. 17, No. 2, Agustus 2024 (pp.156-369)DO - 10.24843/JEKT.2024.v17.i02.p07, 2024)
This study examines small and medium-sized enterprises (SMEs) in Mataram City's creative economy sector to ascertain the effect of payment gateways and financial literacy on SME performance with financial inclusion as an intervention variable. Research design that is quantitative and descriptive is used in this study. Participants in this study were small and medium-sized enterprises (SMEs) from the creative economy who use payment gateways. The sample included a total of fifty participants. The study's sample strategy, known as snowball sampling, was utilized since it was unknown how many SMEs in the creative economy sector used payment gateways. The data source for the primary information will be SMEs themselves. The results of the study show that financial literacy and payment gateways have a considerable beneficial influence on SME performance. They also demonstrate that financial literacy and payment gateways have a significant positive impact on financial inclusion. However, neither financial inclusion as a standalone variable nor as an intervening factor had any effect on SME success.